PEMBERDAYAAN KELOMPOK KADER TB MENINGKATKAN KAPASITAS DIRI DALAM PELAKSANAAN PENGAWASAN MINUM OBAT ANTI TB (OAT) SECARA TERATUR PADA PENDERITA TB PARU FASE LANJUTAN - Aminah, Siti; Tuntun, Maria; Lendawati (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Pulmonary tuberculosis (TB) is an infectious disease commonly found in India, Indonesia, China, the Philippines, and Pakistan. According to the 2021 global report, Indonesia recorded 824,000 TB cases, but only 393,323 cases (48%) were detected, treated, and reported. In Bandar Lampung, with a population of 1,184,949 in 2021, there were 1,463 suspected TB cases in 2022. The case detection rate (CDR) in Bandar Lampung reached 40%, with a cure rate of 43.2% (1,153 patients). There were 48 deaths during treatment (1.8%). In Panjang District, which consists of eight sub-districts, 187 TB cases were identified, with a cure rate of 38.4%. Based on surveys and information from active TB cadres, poor medication adherence is a major factor in low cure rates. Patients often forget to take their medication or stop taking it once they feel better, increasing the risk of multidrug-resistant TB (MDR-TB). The main challenges include a lack of active TB cadres as treatment supervisors (PMOs), the absence of training programs, and the unavailability of a logbook for monitoring treatment. The proposed solution involves recruiting active TB cadres, providing training, offering guidance, and supplying logbooks. The implementation method includes recruitment interviews, cadre training, and mentoring. Each TB cadre is responsible for five TB patients in the continuation phase of treatment. This community service program's outcome was forming a TB cadre group consisting of 10 PMOs in Panjang District. As a result of the cadres' efforts, 45 TB patients (90%) completed their treatment and were declared cured, 3 patients (6%) continued treatment at a referral hospital, and one patient (2%) passed away. This program highlights the vital role of cadres in improving pulmonary TB recovery rates.